THE ROLE OF PROFESSIONAL ETHICS MEDIATION IN THE INFLUENCE OF AUDITOR COMPETENCE AND TASK COMPLEXITY ON AUDIT JUDGMENT IN PUBLIC ACCOUNTING FIRMS IN MEDAN - M. Adrian Patria Erza Nasution; Maya Sari; Irfan Irfan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of auditor competence and task complexity on audit judgment, with professional ethics as an intervening variable. The background of this study is driven by the increasing need for reliable and transparent financial reports, given that these reports are the main basis for investors, creditors, regulators, and other stakeholders in making strategic decisions. Quality audit judgment can only be achieved if auditors have adequate technical competence and experience and can deal with the increasing complexity of audit tasks. In addition, auditors must uphold professional ethics to remain independent, objective, and able to avoid potential conflicts of interest in every decision-making process. This study uses an associative quantitative approach with path analysis using SmartPLS 4.0 software. Data were collected through questionnaires distributed to 80 auditors working at several public accounting firms. The results show that auditor competence and task complexity positively and significantly affect professional ethics. These two variables also have a positive and significant effect on audit judgment. In addition, professional ethics have a positive and significant effect on audit judgment and can mediate the relationship between auditor competence and audit judgment, as well as between task complexity and audit judgment. These findings confirm that the quality of audit judgment is largely determined by a combination of technical competence, experience in managing complexity, and commitment to professional ethics. Thus, this study strengthens the literature on the determinants of audit judgment and provides practical implications for improving audit quality in both the public and private sectors.